(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Strictures of the urethra in men are a widespread pathology that adversely affects the health and, consequently, the quality of life of the patient. The purpose of the study was to assess the nature of the strictures of various departments of the urethra and the frequency of their occurrence in the territory of the Republic of Uzbekistan. The survey data of 195 men (average age - 40.6 ± 13.1 years) who underwent urethroplasty at the Republican Specialized Urology Center JSC from February 2013 to March 2015 were studied. In 46.7% of patients, the strictures were located in the anterior part of the urethra, 53.3%- in the back. The most frequent possible causes of strictures were trauma (38.5%) and infection (22.6%), in 18% of cases the strictures were considered idiopathic, in 19%- iatrogenic. In 13.3% of observations, the strictures were located in the hanging urethra, in 42.7% - in the bulbar, in 32% - in the back. Strictures 28.7% of patients had a length of more than 6 cm, 25.6% - 2 cm or less.